A Review of Issues, Challenges and Prospects of National Development in Nigeria - Garba Aminu, Kabiru (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Despite the huge human material and natural resources at the disposal of Nigeria and after sixty years of independence, the country is still battling with the problems of development. Development could be seen as a critical factor and a desirable phenomenon in the growth and sustenance of any nation. Notwithstanding the few measures taken to develop the country, Nigerian still remains economically immature. This paper takes a good hard look at national development from the perspectives of its associated issues, challenges and prospects. The exploration reviews the degree to which the measures to foster development has been compelling in enhancing the beneficial base of the Nigerian economy for overall national advancement. The paper observes that the Nigerian economy has not essentially aligned towards national improvement. The major issues and challenges highlighted in the paper include corruption, poor policy making and policy instruments, poor infrastructure, and inadequate education. However, regardless of these challenges, the country still has a virtuous prospect for overall national development. One of the major prospects is in the area of basic infrastructural reserve in addition to the abundant human and natural resources left not harnessed in the country.